How do I solve 9(x-4)-7x = 2(3x-2)  

8 Answers | Add Yours

hala718's profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

9(x-4) - 7x = 2(3x-2)

First we will expand the brackets.

==> 9x - 36 - 7x = 6x -4

Now we will combine like terms.

==> 9x -7x -6x = -4 +36

==> -4x = 32

Now we will divide by -4.

==> x = 32/-4 = -8

==> Then, the answer is x = -8

taangerine's profile pic

taangerine | Student, Grade 12 | (Level 1) Valedictorian

Posted on

Distribute the 9 and 2 into their respective groups.

9x-36-7x=6x-4

Combine like terms

-36+4=4x

-32=4x

Divide 4 on both sides to isolate x. 

-8=x or x=-8

 
givingiswinning's profile pic

givingiswinning | Student, Grade 10 | (Level 1) Valedictorian

Posted on

 9(x-4)-7x = 2(3x-2)

9X-36-7x = 6x-4

2x-36=6x-4

-36+4=4x

-32=4x

-8=x

nisarg's profile pic

nisarg | Student, Grade 11 | (Level 1) Valedictorian

Posted on

9(x-4)-7x = 2(3x-2)

9x-36-7x=6x-4

2x-36=6x-4

-36=4x-4

-32=4x

x=-8

jess1999's profile pic

jess1999 | Student, Grade 9 | (Level 1) Valedictorian

Posted on

9 ( x - 4 ) -7x = 2 ( 3x - 2 )

To solve this equation, first distribute

By distributing the equation should look like

9x - 36 - 7x = 6x - 4 now combine the like terms

By combining the like terms, your equation should look like

2x - 36 = 6x - 4 now subtract 2 from both sides

By subtraction, your equation should look like

-36 = 4x - 4 now add 4 on both sides

By adding 4 on both sides, your equation should look like

-32 = 4x now divide 4 on both sides

By dividing, your equation should be

-8 = x which is your answer

atyourservice's profile pic

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

9(x-4)-7x = 2(3x-2)

follow PEMDAS and do the parenthesis first by distributing the numbers in front of them:

9x - 36 - 7x = 6x - 4

now combine liketerms if there are any:

9x - 7x -36 = 6x - 4 

2x - 36 = 6x - 4

move like terms to the same side

-36 + 4 = 6x -2x

-32 = 4x

divide by 4 to get x alone

-32 / 4 = 4x/4

-8 = x

zumba96's profile pic

zumba96 | Student, Grade 11 | (Level 3) Valedictorian

Posted on

9(x-4)-7x = 2(3x-2)

First using PEMDAS distribute x into the equation

9x-36-7x=6x-4

Move the variables on one side

9x-7x-6x=36-4

-4x=32

Divide by -4

x=-8

We’ve answered 318,932 questions. We can answer yours, too.

Ask a question